Electrical Insulation Testing and DGA Analysis for the Diagnosis of Insulation Faults and Failures in 24 MVA Transformers for Distribution Systems - Boonseng, Chongrag; Boonseng, Repeepornpat; Kularbphettong, Kunyanuth (My University, 2020)
The distribution transformers in the electrical system collapse result in damage to industrial property, business, and insurance deductibles. So that to reduce the collapse of the system and the expenses for maintenance. The transformer must be inspected by professional and must be regularly checked. This paper represents the investigation and diagnosis of the 24MVA distribution transformer explosion. The explosion cause the transformer oil to flow through the pressure release value violently. To investigate and diagnose the cause of the transformer explosion, electrical parameters are measured to confirm which parts have been damaged. The result of the measurement shows that there is a fault in the HV coil. Then check the transformer oil by Dissolved Gas Analysis (DGA) method, dating back from 2013 to 2019 and after the explosion. The results can confirm that there has been an abnormality since 2014. The inspection of this transformer shows that every year the electrical parameters and transformer oil inspection and DGA analysis according to IEEE Std C57.104-2019 can prevent an explosion.
Keywords: DGA; diagnostics of insulation; failures of distribution transformer